Urological fistulas after fetal cystoscopic laser ablation of posterior urethral valves: surgical technical aspects. (February 2015) - Sananes, N.; Favre, R.; Koh, C. J.; Zaloszyc, A.; Braun, M. C.; Roth, D. R.; Moog, R.; Becmeur, F.; Belfort, M. A.; Ruano, R.
ABSTRACT Objective To describe the surgical technical aspects associated with the development of urological fistulas after fetal antegrade cystoscopic laser fulguration of the posterior urethral valves (PUV). Methods The perioperative data for all fetal cystoscopies performed between January 2004 and August 2013 at three institutions in the USA, France and Brazil were reviewed, with particular emphasis on surgical technical aspects of the procedure and the complications encountered. Results A total of 40 fetal cystoscopies were performed at the three institutions. Laser fulguration of the PUV was performed in 23 of these cases, with a survival rate of 60.9% (14/23) and normal renal function in 85.7% (12/14) of these infants. Urological fistulas were diagnosed postnatally in four (10%) newborns. The presence of fistulas was associated with a higher gestational age at diagnosis of PUV (P < 0.01) and with the use of semi‐curved rather than curved sheaths (P < 0.01), the use of a diode laser (P < 0.01) and the use of higher laser power and energy (P < 0.01 and P < 0.01, respectively), as well as with less operator experience (P < 0.01) and with absence of fetal anesthesia/immobilization (P = 0.02). Conclusion Urological fistulas are a severe complication of fetal cystoscopic laser fulguration of PUV and are associated with type, energy and power settings of the laser and instrumentation. The use of appropriate technique and proper training of the operator are necessary to perform this fetal intervention safely. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.